Wealth, Greed, and Moral Critique: An Islamic Framework and Forster’s Literary Reflections - MD Munibur Rahman (Indonesian Journal of Islamic Literature and Muslim Society, 2023)
This article examines the phenomenon of wealth obsession and the resulting disillusionment through the lens of Islamic teachings and the insights of Edward Morgan Forster. Drawing on Forster’s essay “My Wood,” this study demonstrates how material possession and the desire for wealth can influence the human psyche, generating an unbounded craving for power and ownership that ultimately leads to dissatisfaction and inner conflict. Islamic teachings, which strongly warn against greed and emphasize moderation in fulfilling human needs, provide a normative framework that aligns with Forster’s critique. Through a textual analysis of Forster’s essay and key Islamic sources, this research finds that individuals often become trapped in the pursuit of wealth without understanding the true limits of their needs. This lack of awareness fuels an endless cycle of ambition. The study concludes that integrating Islamic ethical principles with Forster’s humanistic reflections offers a complementary perspective for overcoming wealth obsession, enabling individuals to attain a more peaceful, balanced, and meaningful life.